Restorative effects and perception of nature-themed artworks in indoor environments: an empirical study based on VR+EEG - Chen, Jiayin; Zhu, Huiqiu; Cheng, Yue; Yin, Henan; Yi, Minzhe; Shen, Danni; Zhang, Zuyao; Wu, Jue (Frontiers in Psychology, 2025)
BackgroundWhile numerous studies have examined the restorative effects of natural elements in indoor environments, limited attention has been given to the role of natural analogues. This study investigates the restorative effects of nature-themed artwork, a common natural analogue in biophilic design.Materials and methodsVirtual reality (VR) was employed to simulate five work environments: rooms featuring nature-themed artwork, a blank foreground, an architectural window view, a natural window view, and a green plant wall, respectively. Measuring content included electroencephalography (EEG), blood pressure, heart rate, and restorative evaluations to compare the effects of these environments on physiological and psychological responses across conditions.ResultsNature-themed artwork significantly reduced systolic blood pressure (p < 0.05), increased alpha wave activity [frontal, central, and occipital regions (p < 0.05), and elicited higher restorative evaluation scores compared to the blank foreground and architectural window view]. Positive correlations were found between α power spectral density (PSD) values and restorative evaluation scores (p < 0.05). Additionally, no significant differences were found between the data induced by nature-themed artworks, the natural window view, and the green plant wall.DiscussionThe results demonstrate that nature-themed artwork exerts restorative effects comparable to direct natural elements (natural window views and green plant walls), surpassing both blank walls and architectural views. This underscores its potential as an effective natural analogue. This study provides reference information for designers involved in interior natural decoration, considering physiological, neural, and psychological aspects.